2007
DOI: 10.1111/j.1600-079x.2007.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves methanol intoxication‐induced oxidative liver injury in rats

Abstract: This study was performed to evaluate the effect of melatonin on methanol-induced liver injury. We evaluated the levels of malondialdehyde (MDA), protein carbonylation (PC), myeloperoxidase (MPO) activities and to assess lipid peroxidation, protein oxidation, neutrophil accumulation and nitrite which is a stable end product of nitric oxide respectively. We also studied superoxide dismutase, catalase, and glutathione peroxidase activities of liver tissue to evaluate the changes in the antioxidant status. Histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
3
15
0
4
Order By: Relevance
“…As mentioned earlier, Galijasevic et al 47 have demonstrated that melatonin acts as a specific inhibitor of MPO under physiological conditions. Studies have shown that melatonin treatment prevents tissue injury by virtue of its ability to not only inhibit oxidative stress but also MPO activity 48,49 . Sener et al 50 have demonstrated that melatonin ameliorates ifosfamide induced renal dysfunction, GSH depletion, MDA accumulation and neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, Galijasevic et al 47 have demonstrated that melatonin acts as a specific inhibitor of MPO under physiological conditions. Studies have shown that melatonin treatment prevents tissue injury by virtue of its ability to not only inhibit oxidative stress but also MPO activity 48,49 . Sener et al 50 have demonstrated that melatonin ameliorates ifosfamide induced renal dysfunction, GSH depletion, MDA accumulation and neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…A strong antioxidant effect of melatonin seems evident as almost all investigators describe that in liver homogenates, melatonin strongly attenuated hepatic LPO [40][41][42][43][44][45][46][47][48][49]102,103,[106][107][108][109][110][111][112][113][114][116][117][118][119][120][121][122][123] , usually measured by means of malondialdehyde quantification. Furthermore, melatonin appears to increase the activity and/or expression of hepatic antioxidant enzymes, such as GSH, GPx and SOD, after most types of injury [40][41][42][43][44][45][46][47][48][49][53][54][55][56][57][58][59][60][61][62][63][97][98][99]…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Rats, mice [100,101] Doxorubicin 10 mg/kg sc for 7 d hLPO↓, GGT/LDH↓ Rats [102] Endosulfan 10 mg/kg ip for 5 d hLPO↓, AST/ALT/LDH↓, hGSH↑, hMPO↓, hTNF-α/IL-1b↓ Rats [103] Iodine 1 mg/kg per day ip for 14 d Hepatic content of Schiff's bases↓ Rats [104] Kainic acid 4-10 mg/kg ip 1 × Hepatic DNA damage↓ Rats [105] Lead 10-30 mg/kg per day ig for 7-30 d hLPO↓, hGSH/hGPx/hSOD↑, hNEC↓ Rats [106,107] Methanol 10 mg/kg ip 2 × hLPO↓, hGSH/hGPx/hSOD/hCAT↑, hMPO/hNO↓ Rats [108] Methotrexate 10 mg/kg per day ip for 5 d hLPO↓, hGSH↑, hNEC↓ Rats [109] Mercury-(Ⅱ) 10 mg/kg ip 2 × hLPO↓, hGSH↑, hMPO↓ Rats [110] α-Naphthylisothiocyanate 10-100 mg/kg ip/po 1-4 × hLPO↓, AST/ALT/LDH/GGT/ALP/BIL↓, hSOD/hCAT↑, hMPO↓ Rats [111][112][113][114] Nodularin 5-15 mg/kg per day ip for 7 d hGPx/hSOD/hCAT↑ Mice [115] Ochratoxin A 5-20 mg/kg ig/po 1-28 × hLPO↓, GGT/ALP↓, hGSH/hGPx/hSOD/hCAT↑, hNEC↓ Rats [116][117][118][119][120] Paraquat 1-10 mg/kg ip 5-6 × hLPO↓, hGSH↑, LD50 of paraquat↑ Rats [121,122] Phosphine 10 mg/kg ip 1 × hLPO↓, hGSH↑ Rats [123] Safrole 0.1-0.2 mg/kg sc 2 × Hepatic DNA damage↓ Rats [124] Thioacetamide 3 mg/kg ip 3-5 × hLPO↓, AST/ALT/LDH/ammonia↓, hGSH/hCAT↑, hiNOS/hNEC↓ Rats [125][126][127] Zymosan 5-50 mg/kg ip 1-7 × hLPO/hMPO↓ Rats [128,129] Cholestasis Bile-duct ligation 0.5-100 mg/kg per day ip/po for 7-13 d hLPO↓, AST/ALT/GGT/ALP/BIL↓, hGSH/hGPx/hSOD/ hCAT↑, hMPO↓, hNO↓, hNEC↓, iron disturbances↓ Rats [130][131][132][133][134][135]…”
Section: Antioxidant Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bir baş ka ça lış ma da mela to ni nin, an ti ok si dan özel li ği ile, me ta no le bağ lı ka ra ci ğer ha sar lan ma sı nı azalt tı ğı gös te ril miş tir. 23 Me ta nol ze hir len me si olan has ta lar, pH<7.0 ise, ma ru zi yet ten son ra >24 sa at geç miş ise, has ta ko ma du ru mun day sa, be ra be rin de opi ad anal je zikle re ma ru zi yet var sa kö tü prog noz lu ka bul edil meli dir. Öte yan dan, er ken baş vu ran, be ra be rin de eta nol al mış olan, cid di me ta bo lik asi doz ve en sefa lo pa ti si ol ma yan ol gu lar iyi prog noz lu dur.…”
Section: Nephrologyunclassified